Resistensi Hubungan Luar Negeri Amerika Serikat dan Iran: Studi Kasus Joint Comprehensive Plan of Action (JCPOA) - Shafar, Wildan Ilmanuarif; Mutmainah, Dian (Jurnal Transformasi Global, 2020)
Since 2015 the United States has been a signatory of the historic nuclear agreement with Iran known formally as the Joint Comprehensive Plan of Action (JCPOA), which was also agreed by other P5+1 countries. JCPOA is the achievement of the U.S. and other P5+1 countries' negotiations with Iran regarding the limitation of Iran's nuclear program. JCPOA is also known to be the vital instrument to reduce Iran's capabilities regarding its aggressive behavior and malign activities, creating destabilization in the Middle East. However, in 2018 the United States government decided to withdraw its participation from the JCPOA. As we know, this decision had an impact on Iran's behavior, which several times violated the contents of the JCPOA agreement even though they did not leave the agreement. We are also witnessing the impact of this decision increase the conflict between the US and Iran in recent years. This research aims to explain the rationale of the U.S. decision to withdraw from the JCPOA nuclear agreement with Iran in 2018. This research using the foreign policy decision-making framework model by Charles W. Kegley and Gregory A. Raymond. This concept focuses on explaining factors of foreign policy decision-making in three sources of analysis and the process of foreign policy-making based on rational choice.